PERAN LEPTIN TERHADAP AKTIVITAS MATURATION-PROMOTING FACTOR(MPF) PADA MATURASI OOSIT - Kakisina, Pieter; Indra, Rasyad (Fakultas Kedokteran Universitas Brawijaya, 2008)
Oocyte maturation is mediated by active Maturation Promoting Factor (MPF) in ooplasma. Maturation Promoting Factor (MPF) is heterodimer protein consists of sub catalytic unit p34cdc2 and sub regulatorunit of cyclin-B. The regulation of maturation promoting factor (MPF) occures throught phosphorylation and dephosphorilation Cdc2 while its activities are controlled by the accumulation and periodical degradation from Cyclin-B during cell cycles development. Leptin inknown has role on oocyte maturation that works at mitogen activated protein kinase (MAPK). MAPK belongs to protein kinase family Ser/Thr that interact with MPF in arranging the progresivennes of oocyte meiosis through the help of c-mos. This interaction is initiated phosphorilation of Ser-369 and Thr-577 in p90rsk. Key words:leptin, MPF, and oocyte maturation.